Nanoparticle "switch-on" by tetrazine triggering. Issue 75 (25th August 2016) - Neumann, Kevin; Jain, Sarthak; Geng, Jin; Bradley, Mark
Abstract : Small-molecule mediated release of drugs from self-assembled nanoparticles through the mediatory of a Diels–Alder reaction. Abstract : This work describes how a small-molecule chemical trigger, reacting through the mediatory of an inverse electron demand Diels–Alder reaction, results in enhanced cellular uptake and selective nanoparticle disintegration and cargo liberation, via gross polymeric morphological alterations. The power of these responsive nanoparticles is demonstrated through encapsulation of the anti-cancer agent doxorubicin and its triggered release, allowing controlled cell death in response to a small-molecule chemical trigger.